2008
DOI: 10.1196/annals.1433.049
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration and Urinary Excretion of Nɛ‐(Carboxymethyl)lysine in Breast Milk– and Formula‐fed Infants

Abstract: Industrial processing of infant formulas (IFs) induces the formation of Maillard products, namely N epsilon-(carboxymethyl)lysine (CML). CML content is expected to be several times higher in IFs than in fresh human breast milk. To elucidate whether CML is absorbed from IFs into the bloodstream, CML concentration in the plasma and urine were analyzed in 6-month-old infants (34 breast fed and 25 fed exclusively with IFs) and in 56 samples of human breast milk and 16 commercial IFs. We found that IFs contain high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 8 publications
6
70
0
5
Order By: Relevance
“…Exogenous AGEs, typically encountered in a Western diet, are at least partially absorbed into circulation where they add to the endogenous AGE level [Uribarri et al, 2005; Somoza et al, 2006; Sebekova et al, 2008; Birlouez‐Aragon et al, 2010]. Among the group of AGEs, N‐ϵ‐carboxymethyl‐ l ‐lysine (CML), a well‐characterized, stable [Ahmed et al, 1986; Kislinger et al, 1999; Uribarri et al, 2010] member, and major epitope of AGE‐modified proteins [Ikeda et al, 1996], has been detected in a wide range of foods, its concentration reaching up to 84.8 mg per average portion size in meat dishes [Hull et al, 2012].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous AGEs, typically encountered in a Western diet, are at least partially absorbed into circulation where they add to the endogenous AGE level [Uribarri et al, 2005; Somoza et al, 2006; Sebekova et al, 2008; Birlouez‐Aragon et al, 2010]. Among the group of AGEs, N‐ϵ‐carboxymethyl‐ l ‐lysine (CML), a well‐characterized, stable [Ahmed et al, 1986; Kislinger et al, 1999; Uribarri et al, 2010] member, and major epitope of AGE‐modified proteins [Ikeda et al, 1996], has been detected in a wide range of foods, its concentration reaching up to 84.8 mg per average portion size in meat dishes [Hull et al, 2012].…”
mentioning
confidence: 99%
“…Similarly, an increase in CML plasma concentrations by 46% was detected in infants fed exclusively infant formulas, high in CML due to heat treatment, compared to breast‐fed infants. In addition, a 60‐fold increase in the urinary excretion of CML was observed, indicating rapid excretion of absorbed CML via urine [Sebekova et al, 2008]. …”
mentioning
confidence: 99%
“…Похожие результаты были полу-чены в двух других исследованиях, в которых опреде-лен средний уровень КМЛ в грудном молоке -3,4 ± 2,4 мкг/г белка [71] и 6,3 ± 4,2 мкг/г белка [72] соот-ветственно. Интересно, что уровень КЛМ в грудном молоке был сопоставим с таковым в смеси, изготов-ленной на основе цельного козьего молока, или был ниже, чем в смесях на основе сывороточных белков коровьего молока [71].…”
Section: российский вестник перинатологии и педиатрии 2018; 63:(4) Runclassified
“…Поэтому в детских смесях на основе гидролиза белков (гидролизатах) обычно определяют более вы-сокие уровни ПРМ, в том числе фурозина и КМЛ, по сравнению со стандартными сухими молочными смесями [71,73]. Кроме того, в составе детских сме-сей присутствуют триглицериды (сложные эфиры глицерина и одноосновных жирных кислот), содер-жащие карбонильные группы, что также вносит свой вклад в образование ПРМ.…”
Section: российский вестник перинатологии и педиатрии 2018; 63:(4) Runclassified
“…It has been shown that the CML content of formulas may increase by 40% throughout the shelf life. Reheating of prepared formula also leads to an increase in the CML content (45,46).…”
Section: Infant Formulas and Glycotoxinsmentioning
confidence: 99%